A flexible approach to transaction management in distributed, multimedia systems - Blair, Gordon S.; Toledo, Maria Beatriz Felgar de (Zielona Góra: Uniwersytet Zielonogórski)
This paper discusses the potential impact of multimedia on one classic distributed systems problem - the provision of transaction mechanisms to support fault tolerance and concurrency control. Several features of distributed multimedia sytems are highlighted: the real-time requirements of continuous media types, the cooperative styles of working and the engineering requirements across the range of media types.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka